THER-02. TARGETING DNA DAMAGE REPAIR IN MYC-DRIVEN PEDIATRIC BRAIN TUMORS. (23rd April 2019) - Krausert, Sonja; Lambo, Sander; Brabetz, Sebastian; Mack, Norman; Schwalm, Benjamin; Pfister, Stefan; Kool, Marcel
Abstract: Pediatric brain tumors frequently harbor MYC - or MYCN -amplification or show high overexpression and are associated with poor outcome. Examples for which current treatments are unsuccessful are for instance the medulloblastoma (MB) subgroups SHH ( MYCN -amplified), Group 3 ( MYC amplified) and embryonal tumors with multilayered rosettes (ETMR). Since MYC(N ) is normally expressed in rapidly dividing cells but not in quiescent tissue stem cells, amplification or high expression in tumors leads to increased transcription, which can be in conflict with DNA replication and subsequently can cause replication stress and DNA damage. We hypothesized that high expression or amplification of MYC(N ) in tumors makes them vulnerable to DNA damage response inhibitors (DDRi) and even more vulnerable to combinations of DDRi and chemotherapeutics. To test this hypothesis we performed in vitro drug experiments using different Group 3 MB cell lines and the BT183 ETMR cell line. We evaluated the IC50-values of the topoisomerase inhibitor Topotecan and the DDRi BGB-290, a PARP-inhibitor, in monotherapy. All cell lines were sensitive for Topotecan and showed IC50-values in the low nM-range but PARP-inhibitors were ineffective (for MB) or showed only slight effects (for ETMR cells). However, a significant decrease in IC50 can be observed when Topotecan and BGB-290 are used in combination. For in vivo treatments, we injected NSG mice with luciferase labelled ETMR cells, monitored tumor growth via IVIS and started the non-toxic single and combination treatments when a predefined threshold of tumor growth was reached. When effective in this ETMR in vivo model, we will repeat the experiments with additional ETMR and MB models. In vivo treatments are ongoing and results will be presented at the conference.